2022
DOI: 10.3390/su142215346
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Support of the Energy Projects as a Part of the Blue Economy Development in the Arctic

Abstract: The article discusses a range of economic issues related to the efficient use of the industrial potential of coastal territories (by the example of the Murmansk region) in the development of shelf deposits. A comprehensive analysis of the industrial complex and an objective assessment of conditions for the development of the oil and gas industry in the Murmansk region are given. Considerable attention is paid to the formation of organizational and economic mechanisms for using the industrial potential of regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Many studies have focused on the issues of sustainable development in the Arctic [3][4][5]86,87,[98][99][100][101][102][103][104][105]. However, it is not possible to define a single system of measures allowing to move away from the resource and raw material model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on the issues of sustainable development in the Arctic [3][4][5]86,87,[98][99][100][101][102][103][104][105]. However, it is not possible to define a single system of measures allowing to move away from the resource and raw material model.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that a colonial model of development is observed in the AZRF [86,87]. This is proven by the high poverty level, lack of direct correlation between the dynamics of GRP, pay growth, average income, and population size (Tables 4-8).…”
Section: Hh Iomentioning
confidence: 97%
“…Within the framework of oil and gas production, due to its specificity of being strictly tied to a certain geographical location, the problem of creating or maintaining and developing already existing infrastructure elements is particularly acute. The Arctic zone of the Russian Federation should be singled out as a separate region, consisting almost entirely of underdeveloped territories of various constituent entities of the Russian Federation, as it is currently of major strategic interest to Russia due to its enormous resource potential [22][23][24].…”
Section: An Overview Of the Characteristics Of Underdeveloped Areas I...mentioning
confidence: 99%
“…To advance the geological exploration of oil-and gas-bearing regions and expand the base of viable hydrocarbon raw materials, it is imperative to enhance the economic efficiency of geological exploration. Maintaining the quality of the subsoil area studies [5] and, more specifically, the environmental safety of the areas that are part of the Russian Federation's Arctic zone (AZRF), are crucial requirements [6,7]. For such activities to take place, cutting-edge technology and techniques for performing fieldwork with the least amount of technogenic influence on the environment must be developed.…”
Section: Introductionmentioning
confidence: 99%